The Effect of Regional Original Income, General Allocation Funds,Specific Allocation Funds, And Fund for The Results of The District Capital Expenditure Allocation And North Sumatra Province City, 2010-2019 - Ira Safitri; Hasibuan, Beby Kendida; Silalahi, Amlys Syahputra; Syahyunan (Journal Of Management Analytical and Solution (JoMAS), 2021)
This study aims to determine the effect of Regional Original Income (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), and Profit Sharing Fund (DBH) on the allocation of Capital Expenditures.  This  research  is  a  causal  associative  design  research  and  the  type  of  data  used  is quantitative data. The data used is obtained from the Regional Budget Realization Report which has been published on the official website as well as from the Regional Government Financial Report (LKPD) document submitted to the Supreme Audit Agency (BPK) of North Sumatra Province. The population of this study were all districts / cities in North Sumatra Province consisting of 25 District Governments and 8 City Governments in the period 2010 to 2019. The sample of this study was determined using saturated sampling. The technique used is multiple linear regression analysis of panel data. The results of this study indicate that simultaneously PAD, DAU, DAK, and DBH have a significant effect on the allocation of capital expenditures in the districts and cities of North Sumatra Province. Partially, PAD has a positive and significant effect on the allocation of capital expenditure, DAU has a positive and significant effect on the allocation of capital expenditure, DAK has a positive and significant effect on the allocation of capital  expenditure,  and  DBH  has  a  positive  and  significant  effect  on  the  allocation  of  capital expenditures in regencies / municipalities of North Sumatra Province the period 2010 to 2019. and DBH has a significant effect on the allocation of Capital Expenditures in the Regencies and Cities of North Sumatra Province. Partially, PAD has a positive and significant effect on the allocation of capital expenditure, DAU has a positive and significant effect on the allocation of capital expenditure, DAK has a positive and significant effect on the allocation of capital expenditure, and DBH has a positive and significant effect on the allocation of capital expenditures in regencies / municipalities of North Sumatra Province the period 2010 to 2019. and DBH has a significant effect on the allocation of Capital Expenditures in the Regencies and Cities of North Sumatra Province. Partially, PAD has a positive and significant effect on the allocation of capital expenditure, DAU has a positive and significant effect on the allocation of capital expenditure, DAK has a positive and significant effect on the allocation of capital expenditure, and DBH has a positive and significant effect on the allocation of capital expenditures in regencies / municipalities of North Sumatra Province the period 2010 to 2019.